Wix, a free website builder as a teaching tool for the enhancement of extensive reading skills to students of first year bachillerato at unidad educativa P.C.E.I. Manuela Saenz, province of Santa Elena, 2015-2016 - Rueda Villa, Aurora del Rocio (2015)
Information and Communication Technologies (ICT) have influenced our society and, more importantly, have caused a great impact on the education field contributing on the acquisition and consolidation of knowledge in students of all ages, as a result, educators have realized its importance becoming tutors along the teaching and learning process. Reading is one of the main skills that a student must acquire; therefore, one of the easiest ways to motivate students is through extensive reading. Extensive Reading is “the reading for pleasure”, it cannot be imposed, it was intended to engage students into the wonderful world of books and stories through the use of a free website builder (Wix), “A website to improve Extensive Reading” as a teaching tool was designed in order to improve this skill outside the classroom. Qualitative, quantitative and inductive-deductive methods were applied; interviews to specialists and survey techniques were implemented as well. The main aim of this research is to demonstrate the improvement of the Extensive Reading skills to students of First year Bachillerato at Unidad Eduactiva P.C.E.I. through the implementation of activities and resources in a friendly Website; after the implementation of the proposal it was evidenced that students developed their Extensive reading skills in 14,17%. It was concluded that ICT have become essential tools that facilitate the teaching-learning process and a free website builder as a teaching tool can contribute to improve the Extensive Reading skill.